2020
DOI: 10.1089/mdr.2020.0089
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Silver Nanoparticles and Vancomycin to Overcome Antibiotic Resistance in Planktonic/Biofilm Cell from Clinical and Animal Source

Abstract: This study aims to evaluate the prevalence of multidrug-resistant (MDR) and biofilm-forming pathogens from animal source compared to clinical ones. In addition, to assess the antibacterial and antibiofilm activity of silver nanoparticles (AgNPs) alone and/or mixed with vancomycin. Out of 62 bacterial isolates from animal respiratory tract infection (RTI), 50.00% were defined as MDR, while among human ones, 44.00% were MDR. The bacteria Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus pneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Characterization of AgNPs was tested by TEM, UV-vis spectroscopy, and DLS. Sizes of AgNPs differ from one study to another [ 25 , 26 ] while the plasmon resonance peak range was nearly similar [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of AgNPs was tested by TEM, UV-vis spectroscopy, and DLS. Sizes of AgNPs differ from one study to another [ 25 , 26 ] while the plasmon resonance peak range was nearly similar [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation P. Aeruginosa ability is an important process for bacterial colonization for persistence (Vallet et al, 2004), making it a problematic issue especially for patients requiring mechanical ventilation and catheterization (Alnour and Ahmed-Abakur, 2017). Inside those biofilms, bacteria became more resistant and difficult to eradicate than the planktonic ones (Mohamed et al, 2018b(Mohamed et al, , 2020a; therefore, this mode of bacterial growth is strongly linked to various diseases at which many bacterial infections are biofilm-related (Mohamed et al, 2019(Mohamed et al, , 2020c.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the antibiofilm efficiency in group D significantly displayed the highest efficacy due to the presence of Cefuroxime-ROE-AgNPs in BIOD cement. Mohamed et al [53] confirmed the anti-biofilm activity of AgNPs alone and in combination with antibiotics. Moreover, the adherence of bacteria was considered to be an important step in the infection [41].…”
Section: Antimicrobial Activitymentioning
confidence: 92%